Subclinical atherogenesis in patients with mild psoriasis: A role for IL-6? - Lise,Michelle Larissa Zini (2017)
Summary Introduction: A link of psoriasis with subclinical atherosclerosis has been postulated and cytokine network might intermediate this association. Few data are available in patients with mild psoriasis. We evaluated carotid intima-media thickness (cIMT) in drug-free psoriatic individuals and controls. In parallel, we searched for associations of cIMT with disease activity indexes and serum interleukins (IL) in psoriatic patients. Method: An experienced radiologist performed the cIMT analyses. Cytokine concentrations were assessed by flow cytometry. Disease activity was evaluated based on psoriasis area and severity index (PASI) as well as body surface area (BSA). Results: Sixty-five (65) patients and 64 controls were studied. Mean age of patients (50.9 years) did not differ from controls (p=0.362). A low PASI and BSA (< 10) prevailed (69.2% and 56.9%, respectively). Median levels of IL-12p70, TNF-α, IL-1β and IL-10 were significantly lower in cases than in controls (adjusted p<0.05), while IL-6 and IL-8 medians did not differ between groups (adjusted p>0.05). Smoking habit and diabetes mellitus predominated in cases (p=0.002). An altered cIMT (≥ 0.9 mm) was more frequent in cases than in controls (23.8% versus 8.5%, adjusted p=0.045). Mean cIMT was higher in cases with a borderline significance (p=0.057). cIMT scores did not correlate to PASI (rs=0.066; p=0.250) or BSA (rs=0.175; p=0.185), but did correlate significantly with serum IL-6 (rs=0.26; p=0.005). Conclusion: Subclinical atherosclerosis was more frequent in patients with mild psoriasis than controls. cIMT in psoriatic individuals correlated with serum IL-6, pointing to an eventual proatherogenic role of IL-6 in these patients. Newer studies should clarify the connection of atherogenesis with cytokines in psoriasis.